2022
DOI: 10.1111/dth.15583
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of apremilast drug survival in psoriasis patients in a daily practice setting: A long‐term experience

Abstract: There is limited evidence about the real‐world survival of apremilast in patients with psoriasis, especially over the long term. To evaluate the long‐term survival of apremilast and its predictive factors when used to treat psoriasis. A retrospective hospital‐based study, including data collected from 104 patients. Survival curves were estimated using the Kaplan–Meier estimator. Proportional hazard Cox regression models were used for multivariate analysis. The average duration of the treatment before discontin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In clinical trials of apremilast, during the long‐term follow‐ups (≥156 weeks) the drug was discontinued in 34.7% of patients owing to lack of efficacy in the study, and in 11.2% of patients it was discontinued owing to adverse events 4 . In real‐world studies that examined the use of apremilast, 1‐year survival rates have been reported to be approximately 30%–50% 5–7 . Moreover, we also reported drug survival for apremilast in 2019, with a 1‐year drug survival rate of 53.4% 8 .…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…In clinical trials of apremilast, during the long‐term follow‐ups (≥156 weeks) the drug was discontinued in 34.7% of patients owing to lack of efficacy in the study, and in 11.2% of patients it was discontinued owing to adverse events 4 . In real‐world studies that examined the use of apremilast, 1‐year survival rates have been reported to be approximately 30%–50% 5–7 . Moreover, we also reported drug survival for apremilast in 2019, with a 1‐year drug survival rate of 53.4% 8 .…”
Section: Introductionmentioning
confidence: 60%
“…The 4-year survival rate in our study was 30%, roughly similar to previous reports, with approximately 20% at 4 years, 5 28.1% at 4 years, 6 and 33% at 5 years. 7 Of 23 patients who discontinued apremilast due to hospital transfer, 13 continued apremilast at their family physicians, therefore the actual continuation rate may have been a little higher. Approximately 49% of patients had one or more adverse events, which was similar to that in real-world data 9,10 and less than that in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation